Effects of mindfulness-and acceptance-based interventions on quality of life, coping, cognition, and mindfulness of people with multiple sclerosis: a systematic review and meta-analysis. Issue 7 (9th August 2022) - Han, Areum
ABSTRACT: This systematic review and meta-analysis of randomized controlled trials (RCTs) examined effects of mindfulness- and acceptance-based interventions (MABIs) on quality of life (QoL), coping, cognition, and mindfulness among people with multiple sclerosis (MS). Four electronic databases were searched to 3 July 2020. Data was combined in a random-effects meta-analysis model. Eighteen RCTs met the eligibility criteria. Meta-analyses at the immediate posttest found: moderate effects of MABIs on QoL, coping, and attention; and a large effect on memory. A large effect of MABIs on QoL was found at follow-up. There was no significant effect of MABIs on mindfulness. Relatively fewer studies in outcomes other than QoL were found, and the overall risk of bias across the included 18 RCTs was unclear. Future high-quality studies with follow-up evaluations are needed to support effects of MABIs on QoL, coping, cognition, and mindfulness in people with MS and examine intervention features that increase and maintain effects.